2021
DOI: 10.31943/mangiferaedu.v6i1.118
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Functional Types and Cotyledons Shape Some Species of Woody Plant

Abstract: ABSTRACT Woody  plant produce small to large seeds which can affect germination process. Cotyledons as an important food source for early growth of seedlings. The position, function, and type of cotyledons when seeds germinate varies. This research aimed to determine cotyledons characters of woody plant seedlings collection  in Bogor Botanic Gardens. The position, function and type  of cotyledons were observed for 65 species of seedlings.This research used an observative method and was analyzed descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This study showed the seed coat was separated from the cotyledons. Epigeal type with seed coat detached from cotyledons is called phanerocotylar (Handayani 2021). According to Handayani (2017Handayani ( , 2019, the type of seed germination from the Annonaceae family is generally epigeal.…”
Section: Monitoring Of Seed Germinationmentioning
confidence: 99%
“…This study showed the seed coat was separated from the cotyledons. Epigeal type with seed coat detached from cotyledons is called phanerocotylar (Handayani 2021). According to Handayani (2017Handayani ( , 2019, the type of seed germination from the Annonaceae family is generally epigeal.…”
Section: Monitoring Of Seed Germinationmentioning
confidence: 99%